Variabilidade espacial e temporal da produtividade, atributos do solo, planta e características físico-químicas de frutos em pomar de peras - Konopatzki, Marcia Regina Siqueira (2011)
The concernment in technical and economic information from some countries grows with the increasing demand for fruits in the world trading. The horticulture, in Paraná state, is an agricultural alternative with a great potential for success. Among the fruits from mild weather, pear (pyrus communis) is the third most consumed and most imported by Brazil. The current consumption is nearly 150 thousand tons per year and production does not reach 10% of total consumption. The extent of the internal market encourages some efforts to increase the national production of fruit, emphasizing, however, technological and economic restrictions to the achievement of such goal. Among the technologies that aim at adding value to the product, IFP (Integrated Fruit Production) and PA (Precision Agriculture) can be highlighted. The association of these techniques can allow a qualitative increase in Brazilian fruits production. In recent years, researches in precision agriculture have been focused on other cultures, besides the cereals that have already been studied, there can be found Precision Horticulture. Thus, this trial aimed at studying spatial and temporal variability of yield as well as physical and chemical properties of soil, plant and physicochemical characteristics of fruits in a pear orchard. The experimental area has 1.24 ha, at coordinates 25° 23' 22" S; 52° 34' 15" W, with an average altitude of 750 m, in Nova Laranjeiras - PR. In the plot, 146 pear trees of Pera D água variety were cropped. The yield variability in the orchard was considered as very high, being characterized as a great heterogeneity. On the other hand, there is a very weak and weak linear correlation with all physical and chemical properties of soil and the chemical characteristics of plants as well as a moderate linear and non-linear correlation with the fruit size. All the studied variables presented structure of spatial dependence, except macroporosity, total porosity (0-20 cm) and fruit density, which allows a site-specific fertilization. The methodology for generation of management zones (MZ) using standard yield was the best one since it has provided the most suitable distribution of MZ in relation to the area management